The transcription factor OsGATA6 regulates rice heading date and grain number per panicle. (5th June 2022) - Zhang, Yan-Jie; Zhang, Yu; Zhang, Liang-Li; He, Jun-Xian; Xue, Hong-Wei; Wang, Jia-Wei; Lin, Wen-Hui
Abstract : OsGATA6 inhibits rice heading and increases grain number through transcriptional regulation of MFT1, and its overexpression has the potential to enhance yield through increasing grain number. Abstract: Heading date, panicle architecture, and grain size are key traits that affect the yield of rice ( Oryza sativa ). Here, we identified a new gene, OsGATA6, whose product regulates heading date. Overexpression of OsGATA6 resulted in delayed heading, increased grain number, and decreased grain size. Knockdown lines generated by artificial microRNA (amiRNA) and CRISPR genome-edited lines of OsGATA6 both showed earlier heading, decreased grain number, and increased grain size. These results suggested that OsGATA6 negatively regulates heading date, positively regulates panicle development, and affects grain size. OsGATA6 was found to be constitutively expressed in rice, and strongly expressed in young leaves and panicles. In situ hybridization analyses showed that OsGATA6 was specifically localized in superficial cells of the panicle primordium. Overexpression lines show decreased expression of RFT1 and Hd3a, which promote heading. OsMFT1, which delays heading date and increases grain number, was down-regulated in amiRNA lines. Further analyses showed that OsGATA6 could bind to the promoter of OsMFT1 and induce its expression, thereby regulating heading date and panicle development. Overexpression of OsGATA6 in Arabidopsis resulted in repressed expression of AtFT and late flowering, suggesting that its function is similar. Taken together, we have identified a new GATA regulator that influences rice heading date and grain number, which potentially increases rice yield.